2011
DOI: 10.1002/cbf.1796
|View full text |Cite
|
Sign up to set email alerts
|

Redox status and pro‐survival/pro‐apoptotic protein expression in the early cardiac hypertrophy induced by experimental hyperthyroidism

Abstract: This study was conducted to analyse the redox status and redox-sensitive proteins that may contribute to a non-genomic mechanism of cardiac hypertrophy induction by hyperthyroidism. Wistar rats, treated with L-thyroxine (T4) during 2 weeks (12 mg·l(-1) in drinking water), presented cardiac hypertrophy (68% higher than control), without signals of liver or lung congestion. Myocardial reduction of the reduced glutathione: oxidized glutathione (GSSG) ratio (45%) (redox status) and elevation in hydrogen peroxide c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 35 publications
(61 reference statements)
2
14
0
Order By: Relevance
“…Interestingly, doxorubicin-induced cardiotoxicity was exacerbated in transgenic mice overexpressing Nrdp1 via enhanced ROS-mediated inhibition of Akt signaling (Zhang et al 2011b), while cardiac hypertrophy in a rat model of experimental hyperthyroidism was associated with increased H 2 O 2 activity generation and downregulation of the Akt pathway (Fernandes et al 2011). Similarly, elevated ROS production in rats subjected to chronic MI was accompanied by decreased phosphorylation of both Akt and GSK-3b in association with significant cardiac hypertrophy and contractile dysfunction (Schenkel et al 2010).…”
Section: Ros-dependent Inactivation Of Akt In Cardiac Remodelingmentioning
confidence: 97%
“…Interestingly, doxorubicin-induced cardiotoxicity was exacerbated in transgenic mice overexpressing Nrdp1 via enhanced ROS-mediated inhibition of Akt signaling (Zhang et al 2011b), while cardiac hypertrophy in a rat model of experimental hyperthyroidism was associated with increased H 2 O 2 activity generation and downregulation of the Akt pathway (Fernandes et al 2011). Similarly, elevated ROS production in rats subjected to chronic MI was accompanied by decreased phosphorylation of both Akt and GSK-3b in association with significant cardiac hypertrophy and contractile dysfunction (Schenkel et al 2010).…”
Section: Ros-dependent Inactivation Of Akt In Cardiac Remodelingmentioning
confidence: 97%
“…THs have also been proposed to act through a nongenomic mechanism, which can occur rather rapidly through binding to a membrane receptor to activate signaling. Thus, cardiac hypertrophy/dysfunction could also be the result of activating signaling pathways through such nongenomic mechanisms where oxidative stress and ROS may serve as potential modulators of this response in hyperthyroidism [22, 24, 42]. …”
Section: Thyroid Hormones and The Heartmentioning
confidence: 99%
“…Conversely, cardiac GPx activity was found to decrease in the hearts of old but not young hyperthyroid rats [45]. On the other hand, Fernandes et al found no significant differences in the cardiac Trx or GSH activities after 2-week treatment of T4 [24]; yet, the same group reported increased Trx [22] but decreased GSH [1820, 22] activities in the hyperthyroid hearts after 4-week treatment in the same model. Additionally, it was reported that T4 [26] but not T3 [48, 53] decreases the cardiac GR activity.…”
Section: Sources Of Increased Oxidative Stress In the Hyperthyroidmentioning
confidence: 99%
See 2 more Smart Citations